SIBIJAK: An Interactive Learning Multimedia Innovation Based on Contextual Teaching and Learning (CTL) - I Made Dika Anggara; Ketut Agustini; I Gde Wawan Sudatha (Universitas Pendidikan Ganesha, 2025)
21st-century education should be implemented by emphasizing the development of student competencies that are relevant to the demands of the times, rather than merely focusing on the mastery of factual knowledge. However, students often find it difficult to understand the material, which hinders the development of their critical thinking skills. In addition, existing learning resources tend to emphasize memorization, making them less engaging. Students show greater interest in learning through interactive digital media and materials connected to real-life contexts. This study aims to develop and test the validity, practicality, and effectiveness of CTL-based interactive multimedia learning to improve the critical thinking skills of 10th grade students in high school. The multimedia, named SIBIJAK (Interactive Learning System for Internet and Computer Networks), was designed using the AM3PU3 model. The validity of the multimedia was measured using instruments based on LORI version 2.0, its practicality was assessed with the UEQ instrument, and its effectiveness was evaluated using a critical thinking test instrument. The results indicate that the multimedia is highly valid, practical with an excellent rating in every aspect, and effective in improving student learning outcomes. The effectiveness test produced an N-Gain score of 0.68 (medium category), with a classical mastery percentage of 84.38% (very good). These findings support the conclusion that CTL-based interactive multimedia can significantly enhance critical thinking skills. The implication of this study is the enrichment of learning media diversity, and most importantly, the development of multimedia that supports students’ 21st-century learning skills.